2020
DOI: 10.1177/1178632920934499
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Client Satisfaction Among Recent Users of Health Services in Lagos, Nigeria

Abstract: Client satisfaction is an important measure of quality of care as it provides information on how well health service providers meet clients’ values and expectations. The study was cross-sectional and analytical in nature. Data were obtained with the use of an interviewer-administered questionnaire. Respondents (n = 994) were a subset of a larger group of community members recruited for a study on quality of health care who had used a health facility for care within 3 months prior to data collection. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The religious distribution of respondents was skewed with 79.4% practicing Christianity and 20.0%, Islam; notwithstanding an almost equal distribution of Christians and Muslims in Lagos State. Other researchers have documented similar ratios of Christian to Muslim participants in Lagos (15,18). Muslim women seeking reproductive health services may prefer non-public facilities for religious reasons.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The religious distribution of respondents was skewed with 79.4% practicing Christianity and 20.0%, Islam; notwithstanding an almost equal distribution of Christians and Muslims in Lagos State. Other researchers have documented similar ratios of Christian to Muslim participants in Lagos (15,18). Muslim women seeking reproductive health services may prefer non-public facilities for religious reasons.…”
Section: Discussionmentioning
confidence: 81%
“…A higher proportion of gynecological patients (95.7%) were satisfied with morning clinic sessions in Akure, Nigeria (16) while 94% of Lagos community members reported satisfaction with services received (18). Another study reported that 96.5% of pregnant women who received care at private and public health facilities within the 3 healthcare levels were satisfied with the care received (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, we found no significant difference in clients’ satisfaction among clients that obtained services from private and those from public owned facilities. Other studies have reported higher satisfaction among clients who attended at private facilities compared to those from public-owned facilities [ 43 , 47 ]. Higher satisfaction within private facilities has been linked with availability of equipment, materials, infrastructures, commodities and motivated staff [ 48 ] and thus readiness for customer service compared to public facilities [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Provision of safe deliveries in Tanzania, the main objective of CEmONC, has been hugely associated with clients’ satisfaction [ 45 , 50 52 ]; therefore, we can associate low client satisfaction at health centres with inadequate quality services. In nutshell, we learned that clients satisfaction is more related to the services provision rather than facility level [ 44 , 47 ].…”
Section: Discussionmentioning
confidence: 99%